Jawaban:
[tex] \sf (3 \frac{1}{5} - 1 \frac{1}{3} ) \times (3 \frac{3}{4} + 1 \frac{1}{2} )[/tex]
[tex] \sf = ( \frac{16}{5} - \frac{4}{3}) \times ( \frac{15}{4} + \frac{3}{2} )[/tex]
[tex] \sf = ( \frac{16 \times 3}{5 \times 3} - \frac{4 \times 5}{3 \times 5} ) \times ( \frac{15}{4} + \frac{3 \times 2}{2 \times 2} )[/tex]
[tex] \sf = ( \frac{48}{15} - \frac{20}{15} ) \times ( \frac{15}{4} + \frac{6}{4} )[/tex]
[tex] \sf = (\frac{28}{15} ) \times (\frac{21}{4} )[/tex]
[tex] \sf = \frac{28 \: \times \: 21}{15 \: \times \: 4} [/tex]
[tex] \sf = \frac{588}{60} [/tex]
[tex] \sf = \frac{49}{5} [/tex]
[tex] \sf = \red{9 \frac{4}{5}} [/tex]
'조슈아' (Svt)
Penjelasan dengan langkah-langkah:
[tex] = (3 \frac{1}{5} - 1 \frac{1}{3} ) \times (3 \frac{3}{4} + 1 \frac{1}{2} )[/tex]
[tex] = ( \frac{16}{5} - \frac{4}{3} ) \times ( \frac{15}{4} + \frac{3}{2} )[/tex]
[tex] = (\frac{48 - 20}{15} ) \times ( \frac{15 + 6}{4} )[/tex]
[tex] = \frac{ \cancel{28}^{ \: 7} }{ \cancel{15}^{ \: 5} } \times \frac{ \cancel{21}^{ \: 7} }{ \cancel {4}^{1} } [/tex]
[tex] = \frac{49}{5} [/tex]
[tex] = \bold{9 \frac{4}{5}} [/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Jawaban:
Penyelesaian :
[tex] \sf (3 \frac{1}{5} - 1 \frac{1}{3} ) \times (3 \frac{3}{4} + 1 \frac{1}{2} )[/tex]
[tex] \sf = ( \frac{16}{5} - \frac{4}{3}) \times ( \frac{15}{4} + \frac{3}{2} )[/tex]
[tex] \sf = ( \frac{16 \times 3}{5 \times 3} - \frac{4 \times 5}{3 \times 5} ) \times ( \frac{15}{4} + \frac{3 \times 2}{2 \times 2} )[/tex]
[tex] \sf = ( \frac{48}{15} - \frac{20}{15} ) \times ( \frac{15}{4} + \frac{6}{4} )[/tex]
[tex] \sf = (\frac{28}{15} ) \times (\frac{21}{4} )[/tex]
[tex] \sf = \frac{28 \: \times \: 21}{15 \: \times \: 4} [/tex]
[tex] \sf = \frac{588}{60} [/tex]
[tex] \sf = \frac{49}{5} [/tex]
[tex] \sf = \red{9 \frac{4}{5}} [/tex]
'조슈아' (Svt)
Penjelasan dengan langkah-langkah:
[tex] = (3 \frac{1}{5} - 1 \frac{1}{3} ) \times (3 \frac{3}{4} + 1 \frac{1}{2} )[/tex]
[tex] = ( \frac{16}{5} - \frac{4}{3} ) \times ( \frac{15}{4} + \frac{3}{2} )[/tex]
[tex] = (\frac{48 - 20}{15} ) \times ( \frac{15 + 6}{4} )[/tex]
[tex] = \frac{ \cancel{28}^{ \: 7} }{ \cancel{15}^{ \: 5} } \times \frac{ \cancel{21}^{ \: 7} }{ \cancel {4}^{1} } [/tex]
[tex] = \frac{49}{5} [/tex]
[tex] = \bold{9 \frac{4}{5}} [/tex]